THE RECLAMATION OF INDUSTRIAL BUILDING VACANCIES: Chicago's Black Community. - Christian, Charles M.; Bennett, Sari J. (Urban Affairs Quarterly, 1977)
This research concerns the extent to which previously vacated industrial building space in Chicago's black community has been reclaimed by industrial and other uses. it encompasses a survey of 209 documented vacancies. Findings reveal that about one-half of the surveyed industrial building vacancies were reclaimed for some specific use, and the balance remained vacant or were demolished. The majority of all reclamations were reclaimed by non-industrial uses. Less intensive use of building space was common in both industrial and non-industrial reclamations. Churches, eating and drinking establishments, auto parts, furniture, and upholstery stores dominated non-industrial reclamations (service establishments presumably oriented to the local black population); industrial reclamations were primarily fabricated metals, construction, printing and publishing, and miscellaneous repair services.